A method of reconstruction after pancreaticoduodenectomy for pancreatic malignancies in very young children: Two cases reports - Angela Inviati; Marco Vito Martino Marino; Olena Kolesnik; Grigoriy Klimnuk; Galyna Shabat; Andrey Lukashenko; Gaspare Gulotta; Sebastiano Bonventre (Elsevier, 2016)
Pancreatic tumors are very rare diseases in very young children. Most information about those diseases in children was published in cases reports. Due to the rare nature of pancreatic tumors in children, there remains the absence of diagnostic algorithms, clear radiographic and morphological assessments as well as evidence based best treatment options. Because of the young age of patients and the rare occurrence of pancreatic neoplasms, tumor detection remains poor. For malignancies affecting the head of the pancreas the only possibility for achieving clear surgical margins is performing a pancreaticoduodenectomy (PD). We describe two cases of diagnostic and treatment of pancreatic tumor of very young children what was done in our institute.